Vibrating-reed studies of flux pinning in the superconducting metallic glass Zr70Cu30 - Esquinazi, P.; Luzuriaga, J.; Durán, C. (American Physical Society, 1988)
Fil: Esquinazi, P. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina